(untitled) (Mwanga wa Lugha, 2025)
The paper analyses avian symbols of power, wisdom and dissension in African leadership delving into Adipo Sidang’s play; Parliament of Owls. The aim of this investigation is to discuss how African leadership has been adulterated symbolically anchored on a postcolonial approach. Adipo Sidang’ in his play he reveals African leadership discourse using avian symbolism to examine the complex roles of leadership, wisdom and discord within African governance. This study focuses on how different bird species such as; the owls, hornbills, parrots and grain-eaters, embody varied aspects of leadership and citizenship. Each of these birds offer insight into the tensions and responsibilities inherent in societal roles. The investigation was anchored on Postcolonial Theory. Two main tenets that guided the analysis are neocolonialism and poor leadership. The research was descriptive, explorative and qualitative in nature. Findings reveal a nuanced portrayal of leadership in conflict with ethical governance as well as a call for societal rebalance. This work will contribute to African literature especially to the canon of postcolonial studies.